(untitled) (Sirte University Journal of Humanities, 2023)
This research explains the original doctrine adopted by the Maliki school of thought, which is the practice of Medina and presented on the basis of the narration of a single individual in case of a conflict between two narrations. As such, it does not contradict the Sunnah or the narrations, but rather it is the correct application of the Sunnah and adherence to the Prophet’s guidance. There is no continuous practice from the time of the Prophet to the time of Imam Malik that contradicts the Sunnah. What is rumored about the Maliki school of thought that it contradicts the Hadith and does not follow the Sunnah and the narrations is incorrect. Some of those who make these rumors even have gone beyond fanaticism to denigrate Medina and its people. They have commented on issues where there is no disagreement. They have not even understood the issue or verified the doctrine and continued to present speculations and guesses.